A Diversification Strategy for South Asia - Lian, Weicheng (IMF Working Papers; Working Paper, 2021)
While South Asia has gone a long way in diversifying their economies, there is substantial scope to do more. Some countries - India, Nepal, and Sri Lanka - can build on their existing production capabilities; others - Bangladesh, Bhutan, and the Maldives - would need to undertake a more concerted push. We identify key policies from a large set of potential determinants that explain the variation in export diversification and complexity across 189 countries from 1962 to 2018. Our analysis suggests that South Asia needs to invest in infrastructure, education, and R and D, facilitate bank credit to productive companies, and open to trade in order to diversify and move up the value chains. Given the COVID-19 pandemic, investing in digital technologies as part of the infrastructure push and improving education are of even greater importance to facilitate the ability to work remotely and assist resource reallocation away from the less viable sectors.